MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN MELALUI MODEL PEMBELAJARAN BERMAIN PERAN PADA SISWA KELAS VI SEKOLAH DASAR - Salim Salim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The background of this research is the low of activity and student achievement which its development is lessencouraging. Therefore this research aimed to overcome the two problems. This research is a class actionresearch with grade VI students as research subject. From the result of the research, it is known that the use ofrole playing learning model can improve student learning outcomes in civic education learning in cycles I asmuch as 2 students (25%) from 8 students, cycle II 6 students (75%), from 8 students, and cycle III all studentscomplete (100%).